An algebra problem

Algebra Level 3

If x = b + c , y = c + a , z = a + b x=b+c, y=c+a , z=a+b , then simplify x 3 + y 3 + z 3 3 x y z a 3 + b 3 + c 3 3 a b c \dfrac{x^3+y^3+z^3-3xyz}{a^3+b^3+c^3-3abc} .

2 0 1 undefined

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

If:

x = b + c x = b + c

y = a + c y = a + c

z = a + b z = a + b

then:

x 3 + y 3 + z 3 3 x y z a 3 + b 3 + c 3 3 a b c = ( a + b ) 3 + ( a + c ) 3 + ( b + c ) 3 3 ( a + b ) ( a + c ) ( b + c ) a 3 + b 3 + c 3 3 a b c = 2 ( a 3 + b 3 + c 3 ) + 3 ( a 2 b + a b 2 + a 2 c + a c 2 + b 2 c + b c 2 ) 3 ( a 2 b + a b 2 + a 2 c + a c 2 + b 2 c + b c 2 + 2 a b c ) a 3 + b 3 + c 3 3 a b c = 2 ( a 3 + b 3 + c 3 3 a b c ) a 3 + b 3 + c 3 3 a b c = 2 \begin{aligned} &\frac{x^3+y^3+z^3-3xyz}{a^3+b^3+c^3-3abc} \\ &= \frac{(a+b)^3+(a+c)^3+(b+c)^3-3(a+b)(a+c)(b+c)}{a^3+b^3+c^3-3abc} \\ &= \frac{2(a^3+b^3+c^3)+3(a^{2}b+ab^2+a^{2}c+ac^{2}+b^{2}c+bc^{2})-3(a^{2}b+ab^2+a^{2}c+ac^{2}+b^{2}c+bc^{2}+2abc)}{a^3+b^3+c^3-3abc} \\ &= \frac{2(a^3+b^3+c^3-3abc)}{a^3+b^3+c^3-3abc} \\ &= 2 \end{aligned}

as required.

Daniel Ferreira
Nov 5, 2016

Suponha que a = 2 \boxed{\mathsf{a = 2}} , b = 3 \boxed{\mathsf{b = 3}} e c = 4 \boxed{\mathsf{c = 4}} . Com efeito, tem-se que:

{ x = b + c x = 3 + 4 x = 7 y = a + c y = 2 + 4 y = 6 z = a + b z = 2 + 3 z = 5 \begin{cases} \mathsf{x = b + c \Rightarrow x = 3 + 4 \Rightarrow \boxed{\mathsf{x = 7}}} \\ \mathsf{y = a + c \Rightarrow y = 2 + 4 \Rightarrow \boxed{\mathsf{y = 6}}} \\ \mathsf{z = a + b \Rightarrow z = 2 + 3 \Rightarrow \boxed{\mathsf{z = 5}}}\end{cases}

Desse modo, basta substituir na expressão...

x 3 + y 3 + z 3 3 x y z a 3 + b 3 + c 3 3 a b c = \mathsf{\frac{x^3 + y^3 + z^3 - 3xyz}{a^3 + b^3 + c^3 - 3abc} =}

7 3 + 6 3 + 5 3 3 7 6 5 2 3 + 3 3 + 4 3 3 2 3 4 = \mathsf{\frac{7^3 + 6^3 + 5^3 - 3 \cdot 7 \cdot 6 \cdot 5}{2^3 + 3^3 + 4^3 - 3 \cdot 2 \cdot 3 \cdot 4} =}

54 27 = 2 \mathsf{\frac{54}{27} =} \\\\\\ \boxed{\boxed{\mathsf{2}}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...